2018
DOI: 10.32861/jssr.spi5.757.763
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Posters as a Learning Media to Improve Student Learning Quality.

Abstract: The aim of the study is to identify the importance of poster as a learning media that can be utilized in learning activities. It also aims to explore the learning outcomes of students who use poster as learning media. In Indonesia, high school students are not allowed to carry a mobile phone, while the school on the other hand, does not provide enough computers for all students. The school computer laboratory could only cater for students need interchangeably. Therefore, teachers in schools choose other media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Newsom et al [28] showed positive student perceptions of its use in classrooms and assessed understanding of library research skills [30]. It is also a strategy used by International Economic Cooperation to improve the quality of learning outcomes [31]. Other studies found that posters can be applied as project assignments, including in public health learning [32], managerial accounting [29], Microbiology [33], and English as a foreign language [15], [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Newsom et al [28] showed positive student perceptions of its use in classrooms and assessed understanding of library research skills [30]. It is also a strategy used by International Economic Cooperation to improve the quality of learning outcomes [31]. Other studies found that posters can be applied as project assignments, including in public health learning [32], managerial accounting [29], Microbiology [33], and English as a foreign language [15], [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The utilization of information and communication technology in learning media improves the quality of learning, it is because it provides information effectively, facilitating the students to understand lesson easily and improve students' creativity. Kemp and Dayton as cited in Harsono et al (2018) pointed out that the use of good instructional media, can enhance the quality of learning and the outcome of learning. Basic competence 3.4 in seventh grade syllabus explained that students are able to identify text structures and language elements of spoken and written transactional interaction texts.…”
Section: Introductionmentioning
confidence: 99%